An Evolutionarily Young Polar Bear (Ursus maritimus) Endogenous Retrovirus Identified from Next Generation Sequence Data - Kyriakos Tsangaras; Jens Mayer; David Alquezar-Planas; Alex Greenwood (Viruses, 2015)
Transcriptome analysis of polar bear (Ursus maritimus) tissues identified sequences with similarity to Porcine Endogenous Retroviruses (PERV). Based on these sequences, four proviral copies and 15 solo long terminal repeats (LTRs) of a newly described endogenous retrovirus were characterized from the polar bear draft genome sequence. Closely related sequences were identified by PCR analysis of brown bear (Ursus arctos) and black bear (Ursus americanus) but were absent in non-Ursinae bear species. The virus was therefore designated UrsusERV. Two distinct groups of LTRs were observed including a recombinant ERV that contained one LTR belonging to each group indicating that genomic invasions by at least two UrsusERV variants have recently occurred. Age estimates based on proviral LTR divergence and conservation of integration sites among ursids suggest the viral group is only a few million years old. The youngest provirus was polar bear specific, had intact open reading frames (ORFs) and could potentially encode functional proteins. Phylogenetic analyses of UrsusERV consensus protein sequences suggest that it is part of a pig, gibbon and koala retrovirus clade. The young age estimates and lineage specificity of the virus suggests UrsusERV is a recent cross species transmission from an unknown reservoir and places the viral group among the youngest of ERVs identified in mammals.